2015
DOI: 10.1007/s00192-015-2770-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ureteral occlusion during transvaginal uterosacral ligament suspension

Abstract: During transvaginal USLS, performance of a concomitant anterior colporrhaphy increased the risk of ureteral occlusion, while the use of a suture-capturing device for suspension suture placement was associated with decreased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…19 There is a possibility that we have under-reported these complications if patients sought care elsewhere in their postoperative course, which is a limitation of a retrospective study design. Ureteral occlusion 20 and postoperative pain 21 are the most common adverse events experienced by women undergoing uterosacral ligament suspension. Although, number of sutures and suture type have not necessarily been correlated with an increased risk of ureteral kinking 19 or pain, our overall lower number of suspension sutures may be a reason for our lower number of complications compared to what is reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…19 There is a possibility that we have under-reported these complications if patients sought care elsewhere in their postoperative course, which is a limitation of a retrospective study design. Ureteral occlusion 20 and postoperative pain 21 are the most common adverse events experienced by women undergoing uterosacral ligament suspension. Although, number of sutures and suture type have not necessarily been correlated with an increased risk of ureteral kinking 19 or pain, our overall lower number of suspension sutures may be a reason for our lower number of complications compared to what is reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This has traditionally been accomplished with SSLF or other vaginal procedures such as uterosacral ligament suspension (USLS). USLS may be easier to perform than SSLF, with less risk of hemorrhage or infection, but does carry a higher risk of ureteral injury especially in patients with concomitant anterior colporrhaphy (22). Moreover, USLS is less practical in treating patients with post-hysterectomy vault prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the rate of ureteral obstructions after SSLF was lower than HUS, while the rate of ureteral obstructions after HUS was 3.7-9% [22]. Jackson [23] et al found that ureteral occlusion was more frequent in those patients undergoing concomitant anterior colporrhaphy. In this study, we used a concomitant pubocervical fascia reconstruction during LSSLF plicated anterior vaginal wall that may pull the ureters toward the anterior vaginal wall, which in turn shortens the distance from the vaginal stump to ureters, and increases the risk of ureteral damage.…”
Section: Sacrospinous Ligament Xation (Sslf)mentioning
confidence: 99%